AB0472 The frequency of methotrexate (MTX) or prednisone discontinuation and of TNF inhibitor (TNFI) discontinuation/switching in rheumatoid arthritis (RA) patients results from 2002-2004 and 2007-2009 in a large us registry. (23rd January 2014) - Kremer, J.; Wenkert, D.; Grant, S.; Xu, P.; Koenig, A.; Collier, D.
Abstract : Background: A greater percentage of RA patients respond to combination therapy with methotrexate (MTX) and a TNFi, than respond to either agent by itself. However, the discontinuation (DC) or withdrawal of MTX, corticosteroids (CS) or biologic agents such as TNFi after prolonged periods of combination treatment, if successful, should benefit RA patients by decreasing expense and exposure to potential side effects. Objectives: To evaluate the frequency of withdrawal of combination treatment within 3 years of initiation by experienced US rheumatologists and whether these practice patterns had changed between '02-'04 and '07-'09. Methods: We compared the recorded incidence of discontinuation of prednisone, and of combined therapy with MTX and TNFi among RA patients (who newly initiatied combination therapy) with at least 3 years of follow-up enrolled in the CORRONA US registry for the periods '02-'04 and '07-'09. We further examined the disease activity during these different periods by CDAI measurement. Infliximab data was not included as its combined use with MTX is mandated. Pts DC'ing a TNFi include those switched to a different TNFi. For the '07-'09 group, some data was available documenting reason for change including: lack of efficacy, toxicity, formulary restriction, pt preference, infection, lack of insurance, and physician preference. Results: 239 patients with 3 yrs of follow-up, initiated combination therapy in '02-'04 compared with 97 in '07-'09. Age and gender were balanced. In the period '02-'04 vs. '07-'09, 63.2% vs. 54.6% of patients had CDAI >10 (Moderate disease) with means of 18.4 and 14.4 respectively (NS). Most patients added TNFi to MTX (63.2% '02-'04 vs. 71.1% '07-'09, NS). Of those RA patients on combination therapy with TNFi and MTX, in '02-'04 vs. '07-'09: 65% vs. 71% stopped MTX and or TNFi; 10.9% vs. 13.4% DC'd MTX only, 33.9% vs. 40.2% discontinued or switched TNFi only and 20.1% vs. 17.5% discontinued both. All comparisons were not significant. Lack of insurance and formulary restriction were recorded as reason for discontinued only in the "discontinued both" group. Of patients on either TNFi and/or MTX in combination with prednisone, in the period '02-'04 vs. '07-'09, 26.8% vs. 35.1% of patients stopped prednisone, this was not statistically significant. Conclusions: Discontinuation/switching of MTX, prednisone and TNFi occurred frequently in the 3 yrs after the initiation of combination therapy. There were no statistical differences in the rate of discontinuation of either MTX or prednisone; or discontinuation/switching of TNFi in the period 2002-2004 vs 2007-2009. Disease activity, by CDAI, trended lower in patients with RA initiating combination therapy in the '07-'09 period, but discontinuation/switching of TNFi trended higher during this time. Dose tapering rates, without discontinuation, will be reported as will discontinuation vs. switch of a TNFi. Disclosure of Interest: J. Kremer Shareholder of: CORRONA, Grant/Research support from: Abbott, Amgen, AstraZeneca, BMS, Genentech, Lilly, Consultant for: Amgen, Genentech, Lilly, Pfizer, Employee of: CORRONA, Speakers Bureau: Abbott, Amgen, BMS, Pfizer, D. Wenkert Shareholder of: Amgen, Employee of: Amgen, S. Grant: None Declared, P. Xu: None Declared, A. Koenig Shareholder of: Pfizer, Employee of: Pfizer, D. Collier Shareholder of: Amgen, Employee of: Amgen